Invasive predatory fish occupies highest trophic position leading to expansion of isotopic niches in a riverine food web - Olivia C. Hodgson; Sydney Stark; Megan K. Schall; Geoffrey D. Smith; Kelly L. Smalling; Tyler Wagner (Ecology, 2025)
Invasive species are drivers of ecological change with the potential to reshape the structure and function of terrestrial and aquatic ecosystems. The invasive flathead catfish ( Pylodictis olivaris ) is an opportunistic predator that has established a rapidly growing population in the Susquehanna River, Pennsylvania, USA, since they were first detected in 2002. Although the predatory effects of invasive catfishes on native fish communities have been documented, the effects of invasion on riverine food webs are poorly understood. This study quantified the effects of invasive flathead catfish on the trophic position (TP) and isotopic niche of the river's food web by comparing invaded and non‐invaded sites. In addition to flathead catfish, the food web components examined included crayfish, minnows, and two ecologically and socioeconomically important fish species: the smallmouth bass ( Micropterus dolomieu ) and channel catfish ( Ictalurus punctatus ). We found that flathead catfish occupied the highest TP, with a posterior mean TP of 3.08 (95% credible interval = [2.71, 3.42]), exceeding that of the two resident fish predators, the smallmouth bass and channel catfish. The TP of the resident channel catfish, which occupies a similar ecological niche, declined after flathead catfish invasion. In fact, there was a 0.92 posterior probability that channel catfish TP was lower in invaded sites than at non‐invaded sites. Using a Bayesian bivariate ellipses analysis, we found overwhelming evidence of isotopic niche expansion and overlap for all components of the food web in the presence of flathead catfish. These findings support the “trophic disruption hypothesis,” where an introduced species prompts resident species to change diets in an attempt to avoid competition and predation following invasion. Our results indicate that flathead catfish invasion is altering food web structure and energy flow in a large riverine ecosystem and contributes to the breadth of knowledge regarding how ecosystems may respond to the introduction of a large predatory fish species.